The Effectiveness of Learning Videos in Improving Student Skills in Land Measuring Science Course 1 - Ridwan Ridwan; Taufik Natsir; Ishak Ishak (Universitas Muhammadiyah Enrekang, 2024)
This study aims to analyze the effectiveness of using learning videos in improving student skills in the course of Land Measurement Science 1. Learning videos are used as interactive media to help students understand the basic concepts of land measurement, especially in the application of measurement techniques in the field. The research method used is quantitative research with an experimental approach. The research subjects were students of the Building Civil Engineering Study Program, Department of Civil Engineering Education and Planning, Faculty of Engineering, Makassar State University. Information collection was carried out through pre-test and post-test followed by the experimental group using learning videos, as well as the control group using conventional learning methods (through Jobsheet guide). The results showed that students who used the learning video showed a significant increase in skills compared to the control group. Thus, the learning video proved to be effective in improving students' concept understanding and practical skills in the Land Measurement Science 1 course.